Principal’s Strategy to Improve Teachers Professional Competence - Atstsaury, Shofian; Hadiyanto, Hadiyanto; Supian, Supian (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
As a leader, the principal has a very large role and duties. The success of a school depends on the strategy implemented by the school principal. This research aims to find out how the principal's strategy is to improve teacher professional competence at Setih Setio 2 Vocational High School Muara Bungo. The method used in this research is descriptive qualitative. The data collection techniques used were observation, interviews, and documentation studies, Meanwhile, data validity testing uses data credibility by conducting triangulation and member checking. The sources were the school principal, deputy head of curriculum, and teachers at Setih Setio 2 Vocational High School Muara Bungo. The results of the study reveal that a good principal's strategy can make it easier to improve teachers professional competence by holding regular meetings with the teachers, always motivating the teachers, conducting competency-based training, maximizing class supervision, and fulfilling the needs for facilities and infrastructure, especially those related to learning.